Techno-economic Study of Recycled Plastic Waste Boards (RPB) as Sustainable Shell Construction Material for Fishing Vessels in Indonesia - Supomo, Heri; Baihaqi, Imam; Safaruddin, Abdul Rahman; Supomo, Wikaranosa (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
The extreme increase in plastic waste over the past few decades has significantly impacted environmental challenges, especially in marine ecosystems. Despite numerous attempts, the use of recycled plastic waste remains restricted to specific applications. This paper experimentally investigates the potential of using Recycled Plastic-Waste Boards (RPB) as a shell hull construction material for fishing vessels in Indonesia. The study technically investigated the performance of RPB works compared to regular materials like wood and fiberglass-reinforced plastic (FRP) for fishing vessels in terms of mechanical properties, and it's cost-effective. The RPB was made from mixed plastic waste, which was collected, chopped into small pieces, and then heated using a special design heating pot which then poured into special mold. The RPB was then mechanically tested using the ASTM D638 standard for tensile strength and the ASTM D790 standard for flexural strength. The results indicate that the RPB’s tensile and flexural strength are 9.4 MPa and 17.22 MPa, respectively, which meets the required mechanical strength standards for marine applications. In addition, the economic analysis shows that using RPB material can lower the construction costs of a 4-GT-sized boat shell hull by 57.79% and 17.09% compared with wood and FRP materials. Based on technical and economic views, the RPB materials have potential as alternative materials for boat shell construction and are more economical. These findings suggest that RPB provides a sustainable alternative to conventional materials and promotes the development of a circular economy within Indonesia's fishing sector. Overall, this research highlights the potential of RPB to contribute to both environmental sustainability and economic feasibility in the construction of small fishing vessels.